The determination of antioxidant and antimicrobial analysis of gaharu essential oil and gaharu leaves in soap formulations / Mohamad Afiq Ikhwan Mohd Noor Velan - Mohd Noor Velan, Mohamad Afiq Ikhwan (2019)
The rapid incorporation of synthetic chemicals in daily personal skin care products is increasing from day to day. The definition of personal skin care product has evolved from the very basic definition of cleansing medium towards the medium to cleanse, transfer scents and conditioning agents, antibacterial agent and antioxidant agents. The bunch of chemicals are added into the products that increase its complexity of interaction between one chemical to another. Therefore, to cope with that situation a bunch of chemicals are added to stabilize the components and to aid in processing. This condition affects the availability of natural skin care products in the market. The aim of this study is to determine the characteristics of natural source towards the development of personal skin care products. The highlight was given on the antioxidant and antibacterial activity of the natural materials. The abundant availability of Gaharu plants and the unique formation of oleoresin make it reliable to be analysed. In this study, the new utilization of gaharu leaves and essential oil was conducted by addition into the soap formulation. Six different soap formulation were prepared using hot process soap making. The analysis in the soap performance was conducted on the soap stability such as appearance attribute, pH and foaming ability. Furthermore, antioxidant and antibacterial abilities was conducted using 2,2-DiphenylPicrylHydrazyl (DPPH) assays and Kirby Bauer Disk Diffusion assay respectively. This study shows that the soap samples added with gaharu essential oil provides a good soap attribute such as appearance, odour and good antioxidant activity while the soap samples added with gaharu leaves yield no added attribute such as good odour and pleasant appearance but possess a good antioxidant free radical scavenging activity of 71.83 percent with the IC 50 of 5.22 mg/ml. The antimicrobial analysis shows highest inhibition of 9 mm and 14 mm for coconut soap subjected to Lactobacillus and E-Coli respectively while olive soap exhibit minimal zone of inhibition of 7 mm and 10 mm respectively. In conclusion, gaharu essential oil and leaves are the suitable alternative to be used as additives in personal skin care products.